Agribusiness Prospect of Banana Flowers and Oyster Mushrooms as Raw Materials of Meatballs Vegetarian - Farida Farida; Wayan Rawiniwati (Universitas Nasional Jakarta, 2021)
Meatballs are one of the popular foods in Indonesia which are generally made from beef meatballs, chicken meat, and fish. However, some Indonesian people like meatballs but cannot consume meat for various reasons, one of which is nutrition and health. Therefore, the author tries to make meatballs made from banana blossoms and oyster mushrooms that can reach that community and are also healthy and nutritious. In this study, the authors determine the right formula between the flower of a banana with oyster mushrooms to get the best taste and quality. Then the authors analyzed the levels of crude fiber, water content, protein content, and organoleptic properties of vegetarian meatballs. After ensuring nutrition, the author also conducted a financial feasibility analysis for this vegetarian meatball. The author's research was conducted at Jalan Bambu Kuning National University Laboratory Center Building, South Jakarta, from December 2013 to June 2014. This research resulted in conclusions that the vegetarian meatball formula with a ratio of 40% banana blossom and 60% oyster mushroom is the best formula and meatball making business. This vegetarian can make a profit of IDR 10,560,000 per month.